2021
DOI: 10.1002/prot.26228
|View full text |Cite
|
Sign up to set email alerts
|

Mapping co‐regulatory interactions among ligand‐binding sites in ryanodine receptor 1

Abstract: Ryanodine receptor 1 (RyR1) is an intracellular calcium ion (Ca 2+ ) release channel required for skeletal muscle contraction. Although cryo-electron microscopy identified binding sites of three coactivators Ca 2+ , ATP, and caffeine (CFF), the mechanism of co-regulation and synergy of these activators is unknown. Here, we report allosteric connections among the three ligand-binding sites and pore region in (i) Ca 2+ bound-closed, (ii) ATP/CFF bound-closed, (iii) Ca 2+ /ATP/CFF bound-closed, and (iv) Ca 2+ /AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Second, a previous study reported that although distributed $10 nm away from RBD, the SARS-CoV-2 polybasic cleavage site can enhance the RBD-ACE2 binding affinity via electrostatic interactions. 43 We conducted a comparative analysis of our approach with Ohm, a well-established method [44][45][46] for mapping allosteric communications. Both methods successfully highlight the significance of K528 in the main allosteric pathway (Figure S4A), aligning with findings from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a previous study reported that although distributed $10 nm away from RBD, the SARS-CoV-2 polybasic cleavage site can enhance the RBD-ACE2 binding affinity via electrostatic interactions. 43 We conducted a comparative analysis of our approach with Ohm, a well-established method [44][45][46] for mapping allosteric communications. Both methods successfully highlight the significance of K528 in the main allosteric pathway (Figure S4A), aligning with findings from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This principle is used in the OHM server for the detection of allosteric pathways (Wang et al, 2020). Previously, analysis of such pathways in RyR1 structures revealed how the cytosolic calcium, ATP, and caffeine activate RyR1 (Chirasani et al, 2022). Here we have used the OHM server to explore the regulatory network of both ion-dependent allosteric pathways.…”
Section: Comparison Of Domain Positions In Different Ryr Statesmentioning
confidence: 99%
“…Both pathways displayed several branches that partially fluctuated among model structures. Notably, most branches comprised residues either of the ATP binding site, known to support the calcium-dependent activation (des Georges et al, 2016;Chirasani et al, 2022), or of the S45 linker, known to participate in the regulation of channel gating (Murayama et al, 2011;Gomez et al, 2016).…”
Section: The Inhibition Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ca 2+ activation site (3667–4253), caffeine-activation site (around W4645) and luminal Ca 2+ sensor (around E4872) are in the vicinity of the four mutation sites and close to the S6/C-terminal domain junction ( Zhang et al, 2014 ; Murayama et al, 2018 ). Allosteric interaction predictions have been used to show that cytoplasmic Ca 2+ and caffeine binding is communicated to the channel gate via a cascade of overlapping interactions that control RyR1 activity ( Chirasani et al, 2021 ) and are likely to similarly influence RyR2 activity.…”
Section: High Resolution Structural Analysis Of Catecholaminergic Pol...mentioning
confidence: 99%